The Characteristics of Unidirectional Solidified Ni-Al-Mo Alloys = Charakterisierung von unidirektional erstarrten Ni-Al-Mo Legierungen - M., Ishak; Takagi, H. (Wiley-VCH, 2012)
The material composite was fabricated by the unidirectional solidification method in the eutectic composition alloy. Performing unidirectional solidification of Ni-Al-Mo alloy in eutectic composition produces γ phase -Ni and γ′ phase-Ni3Al as a matrix, and the phase-Mo growth into fibrous and lamellar-like structure. The aim of this research was to study the characteristics of Ni-Al-Mo after various heat treatment conditions. The specimens were solution-treated at temperatures of 1180°C and 1280°C, followed by water quenching. In addition, aging treatments were carried out at various temperatures (from 700°C to 1000°C) and at different time durations. The microstructure, mechanical properties and characteristics of non-treated, solution-treated and aging specimens were investigated. It was found that the mechanical properties of unidirectional solidified Ni-Al-Mo can be improved by solution treatment whilst the strength through performing an aging treatment. The optimized conditions were at 1280°C and 4 hours for water quenching (solution treatment), followed by an aging process at 800°C and 4 hours. These treatments led to an increase of mechanical properties due to uniformly precipitations of finely dispersed γ′ phase-Ni3Al throughout the specimens.